EDUCAÇÃO DO CAMPO E TRABALHO: QUESTÕES PARA PENSAR A FORMAÇÃO DO EDUCADOR | Countryside education and labor: questions to think about in teacher education (Trabalho & Educação, 2016)
The object of study of this paper is Countryside Education, and its purpose is to discuss its relation to work and education of teachers. This reflection is grounded in the work of the author as coordinator of an undergraduate course on Teacher Education for the Countryside, in the five year period from 2005 to 2015. The theoretical perspective adopted is historical materialism, anchored in authors as Antonio Gramsci and István Mèszáros. What we call Countryside Education in Brazil arises in opposition to the traditional rural education. As grounds for political struggle, the Countryside Education originated in the first decades of the 20th Century, having begun as part of the movement for schools, as well as the fight for its educators to be from or live close to the school spaces where they would teach. Its educating essence is oriented by the practices and ways of living of the people who live in the countryside. The basis of the mentioned contraposition is peasant labor, as well as the social and cultural struggles of the subjects of the countryside, which give meaning to the pedagogical practices of Countryside Education. It is an education turned to all workers, men and women of the rural areas, understood in their diversity of subjects, and taking as reference the way they live and work in the Brazilian countryside. In other words, this kind of education shall uphold and respond to the interests and the sociocultural and economic development of the people who live and work in the fields. One relevant question we have formulated about the relation between Countryside Education and labor is that, in its school forming character, there is a perspective of work as an educational principle.__O artigo tem como objeto a educação do campo e seu objetivo é discutir sua relação com o trabalho e a formação do educador. A base da reflexão vem do trabalho como coordenadora do curso de Licenciatura em Educação do Campo no periodo de 2005 a 2015. O recorte teórico considerado é o materialismo histórico ancorado em autores como: Antonio Gramsci e István Mèszáros. A educação do campo surge em oposição à educação rural. Sua essência formadora é orientada a partir das práticas e das formas do viver do homem do campo. A base dessa contraposição está no trabalho camponês, nas lutas sociais e culturais dos sujeitos do campo. Trata-se de uma educação voltada para o conjunto dos trabalhadores e trabalhadoras do campo, compreendendo-os na diversidade dos sujeitos que são, tendo como referência o modo como vivem e trabalham no meio rural brasileiro. Ou seja, seu significado expressa uma educação que garanta e contemple os interesses e o desenvolvimento sociocultural e econômico dos povos que habitam e trabalham no campo. Uma questão relevante que formulamos sobre a relação entre educação do campo e o trabalho é que, no seu caráter formador escolar, há uma perspectiva do trabalho como principio educativo. Como campo de luta política, a educação do campo data das primeiras décadas do século XX, iniciada pela luta por escolas do campo, bem como pela defesa de que seus educadores sejam e estejam próximo dos espaços escolares onde atuarão como professores.